Sociodemographic and Biological Factors of Health Disparities of Mothers and Their Very Low Birth-Weight Infants. (19th October 2022) - Cho, June; Chien, Lung-Chang; Holditch-Davis, Diane
Abstract : Background: Black mothers and their very low birth-weight infants in the United States have increased risk of adverse neonatal and maternal health outcomes compared with White mothers and infants. Disparities in adverse birth outcomes associated with sociodemographic factors are difficult to quantify and modify, limiting their usefulness in assessing intervention effects. Purpose: To test hypotheses that (1) the biological factors of maternal testosterone and cortisol are associated with sociodemographic factors and (2) both factors are associated with neonatal health and maternal mental health and healthy behaviors between birth and 40 weeks' gestational age. Methods: We used a descriptive, longitudinal design. Eighty-eight mothers and very low birth-weight neonates were recruited from a tertiary medical center in the United States. Data on sociodemographic factors and neonatal health were collected from medical records. Maternal mental health and healthy behaviors were collected with questionnaires. Maternal salivary testosterone and cortisol levels were measured using enzyme immunoassays. Data were analyzed primarily using general linear and mixed models. Results: High testosterone and/or low cortisol levels were associated with younger age, less education, enrollment in a federal assistance program, being unmarried, being Black, poorer neonatal health, and delayed physical growth. Low cortisol level was related to higher levels of depressive symptoms. Black mothers had fewer healthy behaviors than White mothers. Implications for Practice and Research: Findings confirm that biological factors are associated with sociodemographic factors, and both are associated with neonatal health and maternal mental health and healthy behaviors. We propose using sociodemographic and biological factors concurrently to identify risk and develop and evaluate ante- and postpartum interventions. Video abstract available at https://journals.na.lww.com/advancesinneonatalcare/Pages/videogallery.aspx?autoPlay=false&videoId=59